Correction: A highly flexible inorganic framework with amphiphilic amine assemblies as templates. Issue 2 (15th December 2016) - Huang, Hui-Lin; Lin, Hsin-Yau; Chen, Pei-Shan; Lee, Jey-Jau; Kung, Jennifer; Wang, Sue-Lein
Abstract : Correction for 'A highly flexible inorganic framework with amphiphilic amine assemblies as templates' by Hui-Lin Huang et al., Dalton Trans., 2017, DOI: 10.1039/c6dt04165e.